Extruded Lumbar Disc Herniation with Spontaneous Reabsorption: Case Report and Review - Silva, Carlos Eduardo da; Freitas, Paulo Eduardo P. de; Fernandes, Matheus V.; Gomes, Matheus F.; Spassim, Alex; Mesquita, Ademar S., Jr; Cardoso, Geniffer C.; Raupp, Gustavo S.; Olijnyk, Leonardo D. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2016)
Disc herniation is a common condition in the population and has a direct impact on the quality of life in patients, also causing functional limitations in the work place. Treatment protocols include conservative management and/or various surgical interventions. This paper reports on a case of symptomatic large extruded disc herniation, together with spontaneous clinical regression and total re-absorption. We show here conservative management, and a literature review of the main pathophysiological hypotheses for such an unusual evolution.
Keywords: disc herniation; spontaneous regression; disc reabsorption